Influence of the different times milk clotting in production artisanal Minas Frescal cheese - Resende, Suzana Rodrigues; Silva, Kamilla Soares [UNESP]; Borges Machado, Andre Luiz; Peres, Daiane Sousa; Soares, Nayana Ribeiro; Caixeta Garcia, Lismaira Goncalves; Viana, Leticia Fleury; Santos, Priscila Alonso dos (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this study is to evaluate the yield, physico-chemical and microbiological parameters during the shelf life of the Minas Frescal cheese hand-manufactured by family farms. Design/methodology/approach In the milk, analyses of total bacterial counts, somatic cell counts and centesimal composition were performed. The milk coagulation was analyzed, with different curd times (40, 80 and 120 min), with respect to the proximate composition, pH, titratable acidity, yield and microbiological counts. The means were compared using the Tukey test with a significance level of 5 per cent. The most probable number of microorganisms were also determined in water. Findings The results for milk quality were within the requirements established in Normative Instruction 62, except for total dry extract. It was found that curd time did not influence the protein and fat in dry matter contents; however, the ash content in cheese of 40 min of curd time (2.8 g/100g) is significantly higher (p = 0.02) than the values found for the other curd times. The same behavior was observed for moisture content (p = 0.04). The parameters determining the cheese quality were outside the standards for human consumption, but this result is directly related to the water conditions, which were outside of potability levels. To meet the requirements established in the legislation, dairy products must follow strict standards of quality hygiene, both the raw material (water, milk) and their employees who act directly in the process. Originality/value For the preparation of the Minas Frescal cheese, it takes several steps, from obtaining the milk to the product ready to be consumed, so the importance of doing this monitoring and evaluating its quality.
Keywords: Family farming; Quality; Shelf life